2020
DOI: 10.3389/fmicb.2020.02116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight Into the Antifungal Effects of a Fatty Acid Derivative Against Drug-Resistant Fungal Infections

Abstract: The prevalence of drug-resistant pathogenic fungi is a major global health challenge. There is an urgent need for novel drugs that can exert a potent antifungal activity and overcome resistance. Newly discovered anti-fungal properties of existing compounds can potentially offer a rapid solution to address this persistent threat. We rationalized that structures which disrupt the fungal cell membrane could address the above unmet need. As fatty acids underpin the formation and stability of cell membranes, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…On the other hand, treatment of the infected animals with luliconazole was found to decrease the average lesion score of the animals in Group 3 ( Figure 4 A,B). Our findings on the obtained antifungal efficacy of luliconazole (25 mg/kg/day) showed agreement with the existing literature where the control of bacterial infection using luliconazole was equivalent [ 29 ]. Furthermore, treatment of luliconazole spanlastics to the animals in group 4 showed outstanding control of infections as depicted by the significant ( p < 0.0001) reduction in the lesion score with significant reduction in the erythema score when compared to the results obtained in Group 3, treated with luliconazole ( Figure 3 and Figure 4 ).…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, treatment of the infected animals with luliconazole was found to decrease the average lesion score of the animals in Group 3 ( Figure 4 A,B). Our findings on the obtained antifungal efficacy of luliconazole (25 mg/kg/day) showed agreement with the existing literature where the control of bacterial infection using luliconazole was equivalent [ 29 ]. Furthermore, treatment of luliconazole spanlastics to the animals in group 4 showed outstanding control of infections as depicted by the significant ( p < 0.0001) reduction in the lesion score with significant reduction in the erythema score when compared to the results obtained in Group 3, treated with luliconazole ( Figure 3 and Figure 4 ).…”
Section: Resultssupporting
confidence: 91%
“…Such properties could enable its adsorption to the surface membrane, resulting in the alteration of membrane properties and compromising the membrane-associated functions [39,43]. Other related fatty acid derivatives have been hypothesized to cause antifungal activity by penetrating and disrupting the lipid bilayer of fungal cell membranes, increasing membrane fluidity, and causing membrane disintegration and the collapsing of cells [54]. It is plausible that 3-methylbutanoic acid (as a short-chain fatty acid) could cause such effects in the target fungal cells depending on the degree of similarities in the function group and the aliphatic chain length.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that our peptide could indirectly affect membrane integrity. It is widely reported that fatty acids, depending on their properties (i.e., chain length, degree, position and orientation of unsaturation) as well as those of their target, are able to interact with cell membranes ( Bhattacharyya et al, 2020 ), provoking structural perturbation and the consequent loss of functionality ( Liu et al, 2013 ; Bae and Rhee, 2019 ). The upregulation of genes encoding fatty acid synthases in treated P. oryzae cells correlates with membrane rearrangement of to form vesicles and autophagic bodies ( Polyansky et al, 2020 ), observed through the TEM analysis.…”
Section: Discussionmentioning
confidence: 99%